Design features of income-based tax incentives for R&D and innovation - González Cabral, Ana Cinta (OECD Publishing, 2023)
Tax incentives that provide preferential tax treatment to the incomes arising from research and development (R&D) and innovation activities, such as intellectual property regimes, have become widespread in recent years. This paper describes the key design features of tax incentives available in 49 member countries of the Inclusive Framework on BEPS (IF), covering all OECD countries and EU countries. It outlines differences in the design of such incentives that may translate into differences in the tax benefits offered. The information collected and reported in this paper is a first step towards a more systematic comparison of tax support policies for R&D and Innovation
Keywords: Taxation